Judiciary civil liberties and human rights - "Foster, Steven" (Edinburgh, 2006)
This book considers the constitutional position of the judiciary and its role in shaping the individual's relations with the state. Readers will gain the following: *A comprehensive analysis of the history of civil liberties and human rights in the UK, and the judiciary's role in upholding them *An understanding of the Human Rights Act of 1998 and its potential impact on the judiciary's relations with the parliament and the executive *An appreciation of the importance of political accountability and open government in the protection of liberty, together with recent legislative reforms in these areas *An awareness of why important critics believe fundamental freedoms are at risk in the UK in the post 9/11 and 7/7 atmosphere *A chance to draw comparisons between Britain, the USA and European countries in their attempts to create legal frameworks to protect civil liberties and human rights This textbook provides an important, accessible introduction to an area of current widespread concern.Key Features: *Offers a comprehensive introduction to three key issues: human rights legislation, the role of senior judges, and the protection of civil liberties *Guides the reader through complex current debates on public order, covert and mass surveillance, and prevention of terrorism *Provides updated descriptions of key statutes including the Prevention of Terrorism Act 2005 *ssesses contemporary developments in American law and order policy including the USA/ Patriot Act * Summarises the arguments of civil liberties lobbies and successive governments *Includes proposed changes in the law in the aftermath of the July 2005 London bombings
Keywords: Judiciary